Unexplained Methemoglobinemia in Coronavirus Disease 2019: A Case Report. Issue 9 (July 2020) - Faisal, Hina; Bloom, Alexi; Gaber, A. Osama
Abstract : Methemoglobinemia is a rare disorder of the blood in which there is an increase in methemoglobin, which occurs when hemoglobin is present in the oxidized form. Methemoglobin impairs hemoglobin's ability to transport oxygen, produces functional anemia, and leads to tissue hypoxia. We report the successful management of a case of refractory hypoxia due to acutely acquired methemoglobinemia in a patient undergoing treatment for coronavirus disease 2019 (COVID-19) pneumonia. The cause of methemoglobinemia in this patient remains unknown. Hypoxia and methemoglobinemia did not respond to methylene blue and required administration of packed red blood cell transfusions.